1995
DOI: 10.1149/1.2050061
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Texture and Microstructure of Electrogalvanized Layer in Acid Sulfate Solution

Abstract: The crystallographic texture and microstructure of electrogalvanized Zn layers on a mild steel cathode were studied with reference to the galvanizing variables including current density and chloride addition. Increasing the current density reduced the relative density of Zn basal planes parallel to the cathode surface. This phenomenon was attributed to the outgrowth of nonbasal planes within an ion-depleted zone close to the metal substrate surface under high cathode overvoltage induced by the high current den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…In particular, electrodeposition is one of the most commonly practiced industrial techniques for the fabrication of zinc coatings (Panagopoulos et al, 2006;Schlesinger and Paunovic, 2000;Zuniga et al, 2004), routinely producing large quantities of high quality pure Zn coatings for a variety of applications. In recent years, significant research effort has focused on the electrodeposition of zinc coatings from non-toxic acidic electrolytes, where various electrolyte additives have been introduced to improve the deposit properties and morphology (Alfantazi and Dreisinger, 2001;Baik and Fray, 2001;Raeissi et al, 2003;Yim et al, 1995;Youssef et al, 2004a). Additives studied for zinc electrodeposition include glycin (Loto et al, 1992), dextrin (Loto et al, 1992), glycerol (Galvani and Carlos, 1997), thiourea (Li et al, 2007;Youssef et al, 2004b) and gelatin (Baik and Fray, 2001;Saba and Elsherief, 2000;Sekar and Jayakrishnan, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, electrodeposition is one of the most commonly practiced industrial techniques for the fabrication of zinc coatings (Panagopoulos et al, 2006;Schlesinger and Paunovic, 2000;Zuniga et al, 2004), routinely producing large quantities of high quality pure Zn coatings for a variety of applications. In recent years, significant research effort has focused on the electrodeposition of zinc coatings from non-toxic acidic electrolytes, where various electrolyte additives have been introduced to improve the deposit properties and morphology (Alfantazi and Dreisinger, 2001;Baik and Fray, 2001;Raeissi et al, 2003;Yim et al, 1995;Youssef et al, 2004a). Additives studied for zinc electrodeposition include glycin (Loto et al, 1992), dextrin (Loto et al, 1992), glycerol (Galvani and Carlos, 1997), thiourea (Li et al, 2007;Youssef et al, 2004b) and gelatin (Baik and Fray, 2001;Saba and Elsherief, 2000;Sekar and Jayakrishnan, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Chromate conversion coatings further improve the protection, by enhancing the corrosion resistance, particularly by minimizing the formation of white corrosion products as well as providing a colour finish [2]. Deposition of zinc has been widely investigated using various approaches, which effectively lead to the preparation of coatings that differ in their macro and microstructure, texture, density, uniformity and corrosion resistance [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of the texture and morphology of electrodeposited Zn and their variation with electrochemical parameters remains unclear. Yim et al [15] observed a decreasing basal plane (200) with increasing current density in an acid bath. Saber et al [6] obtained a transition in the preferential orientation of the deposits by increasing the current density from pyramidal to high angle (112) to pyramidal (101) passing through prismatic (110).…”
Section: Introductionmentioning
confidence: 98%